ANALISIS RISIKO (K3) DI BENGKEL LAS BUBUT MENGGUNAKAN METODE HAZARD IDENTIFICATION RISK ASSESSMENT (HIRA) - Moh. Syahrul; Andung Jati Nugroho (JURNAL ILMIAH NUSANTARA, 2024)
This study focuses on analyzing Occupational Health and Safety (OHS) risks at the Sarimulya Lathe Welding Workshop using the Hazard Identification Risk Assessment (HIRA) method. This workshop is a small industry with various high-risk activities such as cutting, turning, welding, and grinding. The HIRA method is used to identify potential hazards, assess risk levels based on probability and severity, and propose control measures to mitigate risks. The study results show several potential hazards with varying risk categories. The high-risk category has the largest percentage, 51.85%, spread across various work stages such as the cutting process using oxy acetylene, while the extreme risk category reaches 7.40%, occurring during welding and grinding stages. These risks include accidents from heavy machinery, exposure to fumes and dust, and burns from sparks. Through HIRA analysis, these risks can be assessed, and appropriate control measures determined to improve OHS standards. This research contributes to increasing awareness and compliance with OHS procedures in small industries, particularly at the Sarimulya Lathe Welding Workshop. Improvement suggestions include safety training, regular monitoring of working conditions, and the use of appropriate personal protective equipment (PPE).